2006
DOI: 10.1055/s-2006-950310
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Ylide Based Functionalizations of Tetronic and Tetramic Acids

Abstract: The versatility of the ylide (triphenylphosphoranylidene)ketene (Ph 3 P=C=C=O, 3) in the construction of tetronic and tetramic acids from various carboxylic acid derivatives is demonstrated by new reactions and extensions of known ones. With a-hydroxy or a-amino esters, 3 affords tetronates or tetramates. A twostep synthesis of (-)-epi-blastmycinolactol shows that allyl a-hydroxy esters can be domino Wittig-Claisen reacted to give 3-allyltetronic acids. More extended Wittig-Claisen-Conia cascades can produce 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 45 publications
2
19
0
Order By: Relevance
“…These results indicated that the A/B ring system of tetracycle 14 is more crowded than that of 19. This result clearly indicated that the diradical rearrangement required alower energy than the cis/trans isomerization at D 13 (14) .The physical data of our synthesized products 5 and 6 are identical to those reported in the literature (see the Supporting Information). Thep hysical data of our synthesized products 3 and 4 are identical to those reported in the literature (see the Supporting Information).…”
Section: Angewandte Chemiesupporting
confidence: 85%
See 2 more Smart Citations
“…These results indicated that the A/B ring system of tetracycle 14 is more crowded than that of 19. This result clearly indicated that the diradical rearrangement required alower energy than the cis/trans isomerization at D 13 (14) .The physical data of our synthesized products 5 and 6 are identical to those reported in the literature (see the Supporting Information). Thep hysical data of our synthesized products 3 and 4 are identical to those reported in the literature (see the Supporting Information).…”
Section: Angewandte Chemiesupporting
confidence: 85%
“…[14] It is worth noting that the reaction temperature and the reaction time were critical for the high yield. Heating 15 with (triphenylphosphoranylidene)ketene in mxylene at 160 8 8Cl ed to the acylationo ft he a-hydroxy group and the subsequent intramolecular Wittig reaction to afford tetronic ester 22 in 61 %y ield.…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…The prospects of multi-step, one-pot reactions and reaction cascades incorporating Wittig reagents can be seen in the rich chemistry of ketenylidenetriphenylphosphorane (178) (Scheme 45) [182][183][184][185], which has been reviewed earlier [182,186,187]. Lastly, catalytic Wittig reactions can be seen as a subset of tandem reactions involving phosphoranes.…”
Section: Resultsmentioning
confidence: 99%
“…Natural tetronic acid derivatives with a heterocyclic core of furan-2,4(3H,5H)-dione have antioxidant, 1,2 antiviral, 3,4 antibacterial, 5 and antifungal effects, 6,7 which has attracted the interests of chemists. Many different tetronic acid derivatives have been designed and synthesized, and many of the compounds showed noticeable bioactivity especially when a proper substituent such as an aryl, 8 acyl, 9 and alkyl, 10 (compounds a, b and c, Figure 1) were introduced at the 3-position of furan-2,4-dione.…”
Section: Introductionmentioning
confidence: 99%